Keanekaragaman Gastropoda Sebagai Bioindikator Kualitas Perairan Di Kawasan Industri Kecamatan Pangkalan Susu - Akbar, M. Ali; Khairunnisa; Mardiah; Shinta Sahara, Arini (INSTITUT AGAMA ISLAM NEGERI AMBON, 2024)
Pangkalan susu has an industrial area in the coastal area which has a negativeimpact on water pollution. Gastropods can be used as bioindicators because they are sensitive to environmental changes and have a relatively long life span and can respondto polluted environments, especially water pollution. The aim of this research is to determine the level of water pollution in the industrial area of Pangkalan Susu subdistrict by looking at the gastropod diversity index value. This research uses a survey method with a quantitative descriptive research type. The data collection technique uses purposive sampling with hand collection techniques. The data analysis technique uses the Shanon-Wiener diversity index (H') and looks at the physical and chemical parameters. The results of this research are that industrial area waters are included in moderately polluted waters as seen from the Shanon-Wiener diversity index (H'). The diversity index at station 1 was found to be 1.42 which was classified as moderately polluted, while at station 2 the diversity index value was found to be 2.92 which was in the unpolluted category. This is also influenced by other physical and chemical parameters, namely plant vegetation,temperature, water salinity, pH and substrate. Keywords: Gastropods, Industrial areas, Pangkalan Susu, Pollution